STRUKTUR KOMUNITAS MIKROARTROPODA BRYOFAUNA TERESTRIAL DI TIGA KETINGGIAN YANG BERBEDA DI ZONA MONTANA GUNUNG UNGARAN - Andrei Febrian; Rully Rahadian; Lilih Khotim Perwati (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2013)
Bryofauna is the animal which live in mosses, including microarthtropod. Bryofauna microarthtropod is quite diverse but study about this fauna is rarely done, especially in Indonesia. Bryofauna has unique and specific niche, because it depends on the existence of mosses. The objective of this research is to compare the community structure of bryofauna microarthropod in three different altitude in montane zone, including: bryofauna diversity, abundance, richness and dominance. This research was conducted from April to December 2013. Sampling was conducted at three stations in different altitude, i.e. 1335 m asl, 1660 m asl and 2040 m asl. Sampling was done in purposive way, that means sampling was done only in location contained with mosses. Sampling used quadrat method, with size 1x1m, then the moss samples was taken on quadrat with size 10x10 cm in the 1x1 m quadrat. All samples was extracted using Tullgren Funnel. Bryofauna were identified in Ecology and Biosytematic Laboratorium, UNDIP dan Entomology Laboratorium Zoology Unit, LIPI. Bryofauna Microarthropod that found in montane zone were 7 class, 19 ordo, 44 sub-ordo/family. The dominants taxa on the montane zone are Oribatida and Mesostigmata. The highest bryofauna abundance were found in altitude of 2040 m asl. The highest bryofauna diversity and richnees was found in altitude of 1335 m asl. The highest bryofauna eveness were found in altitude of 1660 m asl. Bryofauna diversity is significantly different on each station. Differences in bryofauna microarthropod community strcuture were influenced by the presence of mosses at each altitude. Keywords : Community structure, bryofauna, microarthropod, montane zone